Comparison and Analysis of Custard Apple Seed Oil with Engine Lubricant (Bio Lubricant). Issue 1 (December 2020) - Ashokkumar, S.; Elanthiraiyan, A; Shagu, S.; Srinivasan, M.; Deepan, K. B.
Abstract: Now a day's the prices are increase and the decline of fossil fuels is generating a great deal of need to find an alternative lubricant from non-edible oil seeds. To order to solve the issue of energy shortages, an alternative energy source must be required. Vegetable oils are perceived to be alternatives to mineral oils for lubricant base oils because of certain inherent technical properties and their biodegradability. Vegetable oils with high oleic contents are considered to be the best alternative to substitute conventional mineral oil-based lubricating oils and synthetic esters. This paper mainly reveals about extraction of oil from custard apple seeds and the study of its composition and physic-chemical properties. Custard apple seeds were tested for their physicochemical properties in the production of biological lubricants. Research indicated that 27.5 percent of oil content in the seeds. The bio lubricant was analyzed for a quality test such as density, viscosity, flashpoint, fire point, calorific value.